Electrolyte and secondary battery
By using an electrolyte containing the compound of formula I and MMDS in a lithium-ion battery, a polymer film is formed to protect the positive electrode interface, which solves the problem of increasing side reactions at high voltage and improves the storage and cycle life of the battery.
Patent Information
- Application Number
- CN202411789781.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Existing high-capacity lithium-ion batteries are prone to side reactions between the positive electrode and the electrolyte at high voltages, resulting in increased gas production and deterioration of storage performance and cycle life.
Using an electrolyte containing lithium salt, solvent, a first additive (compound of formula I) and a second additive (methylene methane disulfonate, MMDS), through these additives, a polymer film is formed on the surface of the positive electrode to enhance the positive electrode interface. mechanical strength and chemical stability reduce side reactions.
It effectively reduces the gas production between the positive electrode and the electrolyte, reduces the irreversible consumption of lithium ions, and improves the storage and cycle life of the battery.
Smart Images

Figure BDA0005179044590000011 
Figure BDA0005179044590000021 
Figure BDA0005179044590000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to an electrolyte and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, power vehicles and energy storage due to their long cycle life, high operating voltage, low self-discharge rate, no memory effect and environmental friendliness.
[0003] At present, the upper limit of the working voltage of the positive electrode materials of high-capacity lithium-ion batteries (such as ternary materials or lithium iron phosphate materials) has been increasing after development and is gradually approaching the material limit. The electronic impedance and polarization of the positive electrode materials increase under high voltage (>3.80V). During the charge and discharge process, lattice collapse caused by uneven lithium desorption is very likely to occur, resulting in side reactions between the positive electrode and the electrolyte and increased gas production, thereby deteriorating the storage performance and cycle life of the battery.
[0004] Therefore, it is necessary to design an electrolyte and a secondary battery to solve the above technical problems. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides an electrolyte and a secondary battery to improve the technical problem that the existing electrolyte is prone to side reactions with high-potential positive electrodes in high-temperature environments, thereby worsening battery gas production.
[0006] To achieve the above-mentioned object and other related objects, the present invention provides an electrolyte, which includes a lithium salt, a solvent, a first additive and a second additive; wherein the first additive includes a compound shown in formula I, and the second additive includes methylene disulfonate;
[0007]
[0008] R1, R2, R3, and R4 in formula I are each independently selected from a substituent having 1 to 6 carbon atoms, 0 to 4 unsaturations, and 0 to 3 heteroatoms, wherein the heteroatom is selected from any one of a nitrogen atom, a sulfur atom, an oxygen atom, a boron atom, and a phosphorus atom.
[0009] In an example of the present invention, in the electrolyte, the mass content of the first additive is 0.05% to 3%, and the mass content of the second additive is 0.1% to 0.8%.
[0010] In an example of the present invention, the mass content of the first additive in the electrolyte is 0.1% to 0.5%.
[0011] In one example of the present invention, R1, R2, R3, and R4 in Formula I are independently selected from alkyl, alkenyl, alkynyl, carbonyl, ester, amino or heterocycle, and the heterocycle is selected from any one of pyrridine, pyrrole, thiophene, thiazole, and furan.
[0012] In one example of the present invention, the compound represented by formula I includes at least one of the following compounds:
[0013]
[0014] In an example of the present invention, the electrolyte further includes a fourth additive, and the fourth additive is selected from at least one of fluoroethylene carbonate, propenyl-1,3-sultone, vinylene ester and tetravinylsilane.
[0015] In one example of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium acetate, lithium methanesulfonate and lithium trifluoromethylsulfonate; the mass content of the lithium salt in the electrolyte is 12% to 17%.
[0016] In one example of the present invention, the solvent includes carbonate and carboxylate; the carbonate is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and fluoroethylene carbonate, and the carboxylate is selected from at least one of ethyl formate, ethyl acetate, propyl acetate and ethyl propionate; the mass content of the solvent in the electrolyte is 70% to 85%, and the mass content of the carboxylate in the electrolyte is above 30%.
[0017] The present invention also provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte described in any one of the above examples.
[0018] In an example of the present invention, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes a lithium iron phosphate material; the solvent of the electrolyte includes a carboxylate, and the mass content of the carboxylate in the electrolyte is greater than 30%.
[0019] In the electrolyte provided by the present invention, by introducing the compound represented by formula I and methylene disulfonate (MMDS) as additives, on the one hand, the tertiary amino group in the compound of formula I is used to adjust the pH value in the electrolyte, so that the chemical environment of the electrolyte is more stable; on the other hand, the property of MMDS to break under high voltage to form methylene and methylene disulfonic acid free radicals is used to induce the copolymerization film-forming reaction of MMDS free radical fragments and the compound of formula I on the surface of the positive electrode, and the mechanical strength and chemical stability of the CEI film on the positive electrode interface are improved by directionally introducing relevant groups into the polymer film formed on the positive electrode interface, so that the CEI film has a good protective effect on the positive electrode during the charge and discharge process, effectively reduces the gas generation of the side reaction between the positive electrode and the electrolyte, reduces the irreversible consumption of lithium ions in the battery, and improves the storage and cycle life of the battery. DETAILED DESCRIPTION
[0020] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0021] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.
[0022] In this document, "multiple", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two. "Further", "further", "particularly", etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present invention.
[0023] In this document, unless otherwise specified, “%” refers to mass percentage.
[0024] In this article, substituents refer to atoms or groups of atoms that replace the main chain or ring in organic compounds. They can replace a hydrogen atom or other atoms in the molecule and affect the chemical and physical properties of the molecule. The type and position of the substituent have an important influence on the reactivity, polarity, solubility and other properties of the molecule.
[0025] Unsaturation, also known as hydrogen deficiency index or ring plus double bond index, is a quantitative indicator of the degree of unsaturation of organic compound molecules. For hydrocarbons with molecular formula CnHm and derivatives of hydrocarbons with molecular formula CnHmOx, if m<2n+2, the hydrocarbon and its hydrocarbon radical have a certain degree of unsaturation Ω, that is, compared with open-chain alkanes with the same number of carbon atoms in the organic compound molecule, the unsaturation of the organic compound increases by 1 for every 2 hydrogen atoms reduced.
[0026] Number of heteroatoms: In organic chemistry, non-carbon atoms are collectively referred to as heteroatoms. The most common heteroatoms are nitrogen atoms, sulfur atoms, and oxygen atoms.
[0027] The first aspect of the present invention provides an electrolyte, which adjusts the pH of the electrolyte by introducing a compound represented by formula I and methylene disulfonate (MMDS) as additives to avoid an increase in the acidity of the electrolyte at high temperatures, thereby improving the chemical stability of the electrolyte; and can also polymerize on the surface of a high-potential positive electrode to form a polymer film with high mechanical strength and high stability, thereby effectively protecting the positive electrode interface, preventing the positive electrode interface from collapsing under high voltage and producing gas by side reactions with the electrolyte, thereby improving the storage and cycle life of the battery.
[0028] The electrolyte includes a lithium salt, a solvent, a first additive, and a second additive. The solvent is the main part of the electrolyte and is used to dissolve the lithium salt and the additive. After the lithium salt is dissolved in the organic solvent, a large amount of active lithium ions can be released, so that the electrolyte has good conductivity. The additive is an auxiliary substance of the electrolyte and can be selected according to actual needs, for example, it can be a film-forming additive, a flame retardant additive, a high voltage additive, etc.
[0029] In the present invention, the first additive includes the compound represented by formula I, and the second additive includes methylene methanedisulfonate (MMDS).
[0030] Wherein, the chemical formula of formula I is as follows:
[0031]
[0032] R1, R2, R3, and R4 in Formula I are independently selected from substituents having 1 to 6 carbon atoms, 0 to 4 unsaturations, and 0 to 3 heteroatoms. That is, the types of substituents R1, R2, R3, and R4 in Formula I do not affect each other, and can be completely identical substituents, or partially identical substituents, such as R1 and R2 are the same or R1, R2, and R3 are the same, etc., or completely different substituents. The number of carbon atoms in the above substituents can be any value from 1 to 6, such as 1, 3, 5, or 6, and the degree of unsaturation can be any value from 0 to 4, such as 0, 1, 3, or 4. Heteroatoms are non-carbon atoms, and heteroatoms are selected from any one of nitrogen (N) atoms, sulfur (S) atoms, oxygen (O) atoms, boron (B) atoms, and phosphorus (P) atoms. For example, heteroatoms can be nitrogen atoms, sulfur atoms, or oxygen atoms, but are not limited thereto. The number of heteroatoms can be any value from 0 to 3. For example, 0, 1, 2 or 3, etc.
[0033] The compound shown in the first additive formula I contains a tertiary amino group (R3N, R represents an alkyl group, and the tertiary amino group is formed by combining a trimethyl group with an amino group (NH2)). The tertiary amino group exhibits alkalinity due to the lone pair of electrons on the nitrogen atom, and can react chemically with acidic substances in the electrolyte (such as acidic substances produced by the decomposition of lithium salts), thereby adjusting the pH of the electrolyte and making the chemical environment of the electrolyte more stable. In addition, the compound molecule shown in formula I also contains an unsaturated double bond. The unsaturated double bond in the compound molecule shown in formula I can be opened under the electric field and oxidative environment of the electrode surface, and copolymerize with other components in the electrolyte (such as solvent molecules, other additives, etc.) to form a polymer film.
[0034] The second additive MMDS, as a sulfur-based additive, breaks under the high voltage at the positive electrode interface to form methylene and methylene disulfonic acid free radicals, and initiates a polymerization reaction with the compound of formula I through the free radicals, thereby forming a polymer film on the positive electrode surface. Due to the polymerization reaction of MMDS and the compound of formula I, functional groups such as amino groups and methylene groups are introduced into the polymer film formed on the positive electrode surface, thereby effectively improving the mechanical strength and chemical stability of the polymer film on the positive electrode surface. Among them, the amine group will introduce hydrogen bonds into the polymer membrane when participating in the polymerization reaction to form a hydrogen bond network in the polymer membrane. These hydrogen bond networks can not only enhance the cohesion and mechanical strength of the polymer membrane, but also help the polymer membrane to maintain integrity at high temperatures; the methylene group is a flexible alkyl chain, which can increase the steric hindrance between polymer chains in the polymer membrane and reduce the close stacking between the chains, thereby improving the flexibility and mechanical strength of the polymer membrane, and the methylene group is relatively stable at high temperatures, which can improve the thermal stability of the polymer membrane; the methylene disulfonic acid group can introduce additional sulfonic acid groups into the polymer membrane during the polymerization reaction. The sulfonic acid group forms a strong ionic interaction with lithium ions, which can effectively enhance the mechanical strength of the polymer membrane, and the sulfonic acid group can further improve the thermal stability of the polymer membrane due to its good heat resistance.
[0035] The polymer film formed by the polymerization of the compound of formula I and MMDS covers the surface of the positive electrode, and based on its own good mechanical strength and chemical stability, it can better resist the volume change and mechanical stress generated during the battery charging and discharging process, and play a good protective role on the positive electrode surface, effectively reducing the side reactions caused by the contact between the positive electrode and the electrolyte, reducing the irreversible consumption of active lithium ions in the battery, and reducing the gas production of the battery. In addition, the polymerization reaction of MMDS and the compound of formula I also introduces tertiary amino groups into the polymer film on the surface of the positive electrode to slow down the increase in impedance caused by the reduction of tertiary amino groups in the electrolyte to generate excess lithium nitride on the surface of the negative electrode.
[0036] In some embodiments, the mass content of the first additive in the electrolyte is any value between 0.05% and 3%, for example, it can be 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.7%, 1%, 1.5%, 2%, 2.5% or 3%. Optionally, the mass content of the first additive in the electrolyte is any value between 0.1% and 0.5%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. The inventors have found that when the content of the first additive in the electrolyte is limited to the above range, it can promote the formation of a solid electrolyte interface film (Cathode Electrolyte Interphase, CEI) with stable properties and suitable thickness at the positive electrode interface, thereby taking into account the mechanical strength and chemical stability of the CEI film without excessively increasing the battery impedance. When the mass content of the first additive in the electrolyte is too small, a CEI film of sufficient thickness cannot be formed at the positive electrode interface, and the protection effect on the positive electrode is poor. When the content of the first additive in the electrolyte is too much, the CEI film formed at the positive electrode interface is too thick, thereby affecting the ionic conductivity of the positive electrode and having a negative impact on the cycle performance of the battery.
[0037] In some embodiments, the mass content of the second additive in the electrolyte is any value between 0.1% and 0.8%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%. The inventors have found that when the second additive is limited to the above range, the structural strength of the CEI film formed at the positive electrode interface can be effectively enhanced without excessively increasing the thickness of the CEI film. If the addition amount of the second additive MMDS is higher than 0.8%, the thickness of the formed CEI film is thicker, which is not good for the battery dynamics and interface stability, thereby affecting the cycle performance of the battery.
[0038] In some embodiments, R1, R2, R3, and R4 in the compound of formula I are independently selected from alkyl, alkenyl, alkynyl, carbonyl, ester, amino, or heterocyclic. Wherein, heterocyclic means that the atoms constituting the ring include at least one non-carbon atom in addition to carbon atoms, and these non-carbon atoms are heteroatoms. As an example, heterocyclic includes but is not limited to any one of pyridine, pyrrole, thiophene, thiazole, and furan. For example, the heterocyclic can be pyridine, thiophene, or furan, etc. That is, R1, R2, R3, and R4 can all be selected from any one of alkyl, alkenyl, alkynyl, carbonyl, ester, amino, and heterocyclic, and can be all the same, partially the same, or not the same. As an example, R1, R2, R3, and R4 can all be alkyl; or R1 and R2 are alkyl, R3 is alkenyl, and R4 is alkynyl; or R1 is alkyl, R2 is ester, R3 is amino, and R4 is alkenyl; and so on.
[0039] In some embodiments, the compound represented by Formula I is selected from at least one of Compound I-1, Compound I-2, Compound I-3 and Compound I-4. Optionally, the compound represented by Formula I is selected from Compound I-1. The chemical formulas of Compound I-1, Compound I-2, Compound I-3 and Compound I-4 are as follows:
[0040]
[0041] In some embodiments, the electrolyte further includes a third additive, which is selected from at least one of fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), vinylene ester (VC) and tetravinylsilane (TVSi). The third additive helps to form a stable solid electrolyte interface film (Solid Electrolyte Interphase, SEI) at the negative electrode interface, which can further enhance the film-forming effect of the electrolyte at the negative electrode interface, enhance the protective effect on the negative electrode interface, and improve the charge and discharge cycle performance of the battery.
[0042] In some embodiments, the third additive is selected from one or a combination of two of FEC, PST, VC, and TVSi, and the mass content of each type of additive in the third additive in the electrolyte is any value in the range of 0.05% to 3%, for example, it can be 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.3%, 2.5%, 2.7% or 3%. When the mass content of each type of additive in the third additive in the electrolyte is within the above range, it can promote the formation of SEI film at the negative electrode interface without excessively increasing the impedance of the battery. When the content of each type of additive in the third additive in the electrolyte is too little, it will lead to insufficient film formation of SEI film at the negative electrode interface, making it difficult to effectively protect the negative electrode, thereby negatively affecting the cycle capacity of the battery; when the content of each type of additive in the third additive in the electrolyte is too much, it will lead to excessively high impedance of SEI film at the negative electrode interface, which will have a negative impact on the battery cycle performance.
[0043] In addition, it should be noted that the lithium salt in the electrolyte can be selected from conventional lithium salts in the art. As an example, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethyl)sulfonyl imide (LiFSI), lithium bis(trifluoromethyl)sulfonyl imide (LiTFSI), lithium acetate (CH3COOLi), lithium methane sulfonate (CH3SO3Li) and lithium trifluoromethyl sulfonate (CF3SO3Li). Preferably, the lithium salt is selected from lithium hexafluorophosphate (LiPF6) with good comprehensive performance, or lithium hexafluorophosphate (LiPF6) is mainly used, and other lithium salts are added in appropriate amounts to take advantage of the advantages and improve the performance of the electrolyte. In some embodiments, the mass percentage of the lithium salt in the electrolyte is any value between 12% and 17%, for example, it can be 12%, 13%, 14%, 15%, 16% or 17%. For example, in one example, the lithium salt includes lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI), and the mass ratio of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) in the electrolyte is (1-14):(1-16).
[0044] The solvent in the electrolyte can be selected from conventional solvents suitable for lithium-ion batteries in the art. The solvent includes at least one of carbonate and carboxylate, wherein the carbonate is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (EMC) and fluoroethylene carbonate (FEC), and the carboxylate is selected from one or more of ethyl formate (EF), ethyl acetate (EA), propyl acetate (PA) and ethyl propionate (EP). That is, the solvent can be selected from any one of the above-mentioned solvents, or any two or a combination of two. As an example, the solvent is a combination of EF and EC, a combination of EC, DMC and EMC, or a combination of EC, DMC, PC and EA, and so on. In some embodiments, the solvent includes at least carbonate and carboxylate, and the mass content of the solvent in the electrolyte is generally 70% to 85%, for example, 70%, 75%, 80%, 81%, 83% or 85%, etc.
[0045] Generally, the gas production problem of the positive electrode material with a layered structure or a spinel structure is serious at high temperature, while the structural problem of the positive electrode material with an olivine structure is not serious in the gas production problem in the battery. However, the inventors have found that when the positive electrode material with an olivine structure (such as a lithium iron phosphate material) is matched with a high-content carboxylate solvent, the side reaction between the two increases the gas production, so that the battery equipped with lithium iron phosphate also faces a serious gas production problem. In view of the above problems, the electrolyte provided by the present invention forms a CEI film on the surface of the positive electrode through the first additive formula I compound and the second additive MMDS to isolate the contact reaction between the positive electrode and the electrolyte; at the same time, the carbonyl group of the carboxylate can be introduced into the formed CEI film during the polymerization film formation to form a site for lithium ion binding in the CEI film, thereby reducing the ion conduction impedance of the CEI film, thereby effectively improving the gas production problem of the high carboxylate electrolyte battery.
[0046] In addition, in some implementations, the solvent may further include at least one of ethers and nitriles, wherein the ethers are selected from ethylene glycol dimethyl ether and / or diethanol diethyl ether, and the nitriles include one or more of acetonitrile, propionitrile, butyronitrile, and valeronitrile.
[0047] The electrolyte of the present invention can be prepared according to conventional preparation methods. For example, the electrolyte is prepared in a glove box, the argon or nitrogen content in the glove box is 99.999%, the actual oxygen content in the glove box is 0.1ppm, and the moisture content is less than 10ppm. In the glove box, after the solvent is mixed evenly according to the set ratio, the fully dried lithium salt and additives are added to the above solvent, mixed evenly, and prepared into an electrolyte. Among them, the content of each component in the electrolyte is the weight percentage calculated based on the total weight of the electrolyte.
[0048] The present invention also provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte described in any of the above embodiments. During the battery charging and discharging process, lithium ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrolyte plays a role in conducting lithium ions between the positive electrode sheet and the negative electrode sheet. It should be noted that the structural type of the above-mentioned secondary battery is not limited, and the secondary battery can be any conventional structure of the secondary battery on the market, such as a soft-pack battery, a square shell battery or a cylindrical battery.
[0049] In addition, the secondary battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecrafts, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0050] The composition and preparation method of the secondary battery are described in detail below:
[0051] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. Among them, the positive current collector is, for example, a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Among them, the thickness of the positive current collector is, for example, 8μm-15μm. In one embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive current collector has two surfaces opposite to each other in its own thickness direction, and the positive active material layer is disposed on any one or both of the two opposite surfaces of the positive current collector. The positive active material layer includes a positive active material, a positive conductive agent and a positive binder. There is no specific restriction on the positive active material, the positive conductive agent and the positive binder here, and those skilled in the art can choose according to actual needs.
[0052] The positive electrode active material can be selected from any material suitable for lithium-ion batteries, that is, any compound that can reversibly embed and deintercalate lithium ions can be used. As an example, the positive electrode active material can be selected from ternary materials, lithium-containing phosphates, and spinel materials, wherein the ternary materials include lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide doped with metal ions, lithium nickel cobalt aluminum oxide doped with metal ions, etc.; lithium-containing phosphates include lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The binder of the positive electrode is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate (Polyacrylate), polyvinyl ether (Polyvinylether), polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene (Polyhexafluoropropylene) or styrene butadiene rubber (Polymerized Styrene Butadiene Rubber, SBR), etc. The positive electrode conductive agent is, for example, one selected from carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more selected from the group consisting of ... in any proportion.
[0053] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector can be made of a material with good electrical conductivity and mechanical strength, such as copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a thickener. The specific types of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder are not specifically limited here. Materials known in the art that can be used in lithium-ion batteries can be used, and those skilled in the art can select according to actual needs.
[0054] The negative electrode active material is selected from compounds capable of intercalating and deintercalating lithium ions. As an example, the negative electrode active material is selected from one or more combinations of carbon-based materials and silicon-based materials. Carbon-based materials include, for example, soft carbon, hard carbon, artificial graphite, natural graphite, etc., and silicon-based materials include, for example, elemental silicon, silicon oxide compounds, silicon carbon compounds, etc. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), or a combination of several mixed in any proportion; the thickener is selected from sodium carboxymethyl cellulose CMC-Na or lithium carboxymethyl cellulose CMC-Li.
[0055] The diaphragm is selected from conventional types in the art, such as polyethylene film (PE), polypropylene film (PP), glass fiber film, polyethylene film or composite film, etc. The thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.
[0056] The battery assembly is carried out according to conventional methods, for example: after preparation, the negative electrode sheet, the separator, and the positive electrode sheet are stacked and wound in sequence, so that the separator is located between the positive and negative electrodes to play a role of isolation. Then the electrode assembly formed by winding or stacking is packaged into a shell, transferred to a vacuum oven at 120°C for drying, and the above-prepared electrolyte 3.0g / Ah is injected and then sealed, and the electrolyte is formed, and finally a lithium-ion battery with a capacity of 1Ah is prepared.
[0057] In some embodiments, the secondary battery uses a positive electrode active material with a high upper limit of the working voltage (such as >3.80V), such as a high nickel ternary material or a lithium iron phosphate material. Although the use of the above-mentioned positive electrode active material can improve the battery capacity and fast charging performance, it is also easy to cause lattice collapse caused by uneven lithium desorption during the charging and discharging process, and the side reactions with the electrolyte increase, resulting in active material loss. The electrolyte in the above-mentioned embodiment used in the secondary battery can effectively protect the positive electrode interface, and can further improve the cycle life of the battery compared to the prior art. In one example, the positive electrode active material in the secondary battery is selected from lithium iron phosphate material, and the solvent of the electrolyte includes a carboxylate with a mass content of more than 30%. The lithium iron phosphate material not only has the problem of unstable kinetic performance of high-voltage positive electrode materials, but also has side reactions with high-content carboxylate in the electrolyte under high temperature environment (>45°C), increasing the acidity of the electrolyte and gas production of the battery. The secondary battery using the electrolyte in the above embodiment can use the first additive to effectively adjust the pH of the electrolyte, improve the chemical stability of the electrolyte, and can cooperate with the second additive to form a CEI film on the positive electrode surface to achieve effective protection of the positive electrode interface without excessively affecting the ion exchange capacity of the positive electrode interface, thereby effectively reducing battery gas production.
[0058] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.
[0059] Example 1
[0060] This embodiment provides an electrolyte, which includes a lithium salt, a solvent, a first additive, a second additive, and a third additive. Wherein, the solvent is a composition of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), and ethyl acetate (EA), and the volume ratio of the four is EC: DMC: PC: EA = 2.5: 1: 0.5: 6; the lithium salt is a composition of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI), and the mass content of the lithium salt in the electrolyte is 15%, the mass content of LiPF6 is 9%, and the mass content of LiFSI is 6%; the first additive is a compound shown in formula I-1, and the mass content of the first additive in the electrolyte is 0.3%, the second additive is methylene disulfonate (MMDS), and the mass content of the second additive in the electrolyte is 0.5%, and the third additive includes vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and the mass content of VC in the electrolyte is 3%, and the mass content of FEC in the electrolyte is 0.5%.
[0061] The preparation process of the electrolyte is as follows: In an argon atmosphere glove box with a water content of <10ppm, first mix EC, DMC, PC, and EA in a volume ratio of 2.5:1:0.5:6 to form a solvent; then add lithium salts LiPF6 and LiFSI and additives to the solvent, and mix them evenly to obtain a non-aqueous electrolyte. Among them, the addition amount of LiPF6 and is 9% of the total weight of the electrolyte, the addition amount of LiFSI is 6% of the total weight of the electrolyte, the addition amount of the first additive formula I-1 compound is 0.3% of the total weight of the electrolyte, the addition amount of the second additive MMDS compound is 0.5% of the total weight of the electrolyte, the addition amount of VC in the third additive is 3% of the total weight of the electrolyte, and the addition amount of FEC in the third additive is 0.5% of the total weight of the electrolyte.
[0062] Example 2
[0063] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass content of the first additive in the electrolyte is adjusted to 0.05%, and the mass content of the second additive in the electrolyte is adjusted to 0.3%.
[0064] Example 3
[0065] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass content of the first additive in the electrolyte is adjusted to 3%, and the mass content of the second additive in the electrolyte is adjusted to 0.3%.
[0066] Example 4
[0067] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass content of the second additive in the electrolyte is adjusted to 0.1%.
[0068] Example 5
[0069] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass content of the second additive in the electrolyte is adjusted to 0.8%.
[0070] Example 6
[0071] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the compound represented by Formula I-2 is used as the first additive.
[0072] Example 7
[0073] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the compound represented by Formula I-3 is used as the first additive.
[0074] Example 8
[0075] This embodiment provides an electrolyte of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that the compound represented by Formula I-4 is used as the first additive.
[0076] Comparative Example 1
[0077] This comparative example provides an electrolyte of the same system as that of Example 1. The difference between this comparative example and Example 1 is that the first additive compound of formula I and the second additive MMDS are not added to the electrolyte.
[0078] Comparative Example 2
[0079] This comparative example provides an electrolyte of the same system as that of Example 1. The difference between this comparative example and Example 1 is that the second additive MMDS is not added to the electrolyte.
[0080] Comparative Example 3
[0081] This comparative example provides an electrolyte of the same system as that of Example 1. The difference between this comparative example and Example 1 is that the first additive, the compound of formula I, is not added to the electrolyte.
[0082] The electrolytes prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were respectively assembled in lithium ion secondary batteries, and the lithium ion batteries were tested to verify the efficacy of the present invention. The preparation process of the lithium ion secondary battery is as follows:
[0083] Preparation of positive electrode sheet: Mix the positive electrode active material LiFePO4, the positive electrode binder polyvinylidene fluoride and the positive electrode conductive agent Super P in a mass ratio of 97:1:2, add the solvent N-methylpyrrolidone, and stir until it is uniform and transparent under the action of a vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on an aluminum foil, and the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0084] Preparation of negative electrode sheets: Mix the negative electrode active material artificial graphite, the negative electrode conductive agent Super P, the negative electrode thickener sodium carboxymethyl cellulose (CMC-Na), and the negative electrode binder styrene-butadiene rubber (SBR) in a mass ratio of 96:1:1:2, add deionized water and fully stir until uniform under the action of a vacuum mixer to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector copper foil, dry it at room temperature, and then transfer it to an oven for drying, and obtain a negative electrode sheet through cold pressing, slitting and other processes.
[0085] Selection of diaphragm: A polypropylene film with a thickness of 12 μm was used as the diaphragm.
[0086] Preparation of battery: Place the positive electrode sheet, separator, and negative electrode sheet in order, with the separator between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind to form a bare battery cell. Then wrap it with aluminum plastic film, transfer it to a vacuum oven and dry it at 120°C, inject the above-prepared electrolyte at 3.0g / Ah, seal it, and perform electrolyte formation to obtain a soft-pack lithium-ion battery with a capacity of 1Ah.
[0087] The performance test was performed on the lithium ion batteries assembled with the electrolytes provided in Examples 1 to 8 and Comparative Examples 1 to 3, wherein the electrolyte parameters and test results of Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1, and the test method is as follows:
[0088] The battery gas production performance test includes: testing the initial volume V1 of the battery after fully charging it, then storing it in a 60°C high temperature cabinet, recharging and testing the volume every 7 days, and after 28 days, the battery cell volume is tested to be V2, and (V2-V1) / V1 is the gas production growth rate.
[0089] Table 1: Performance test results of electrolyte assembled batteries in Examples 1 to 8 and Comparative Examples 1 to 3
[0090]
[0091] The contents in Table 1 are all the mass percentages of the components relative to the electrolyte.
[0092] By comparing the test results of Examples 1 to 8 and Comparative Example 1, it can be seen that the use of the compound of formula I and MMDS as additives in the electrolyte can not only inhibit the acidification of the electrolyte at high temperature and improve the chemical stability of the electrolyte, but also form a CEI film with both mechanical strength and thermal stability at the positive electrode interface, isolating the contact side reaction between the positive electrode and the electrolyte, and more effectively inhibiting the gas production of the battery than Comparative Example 1.
[0093] By comparing the test results of Example 1 with Comparative Examples 2 to 3, it can be seen that compared with using only the compound of formula I as an additive in Comparative Example 2, or using only MMDS as an additive in Comparative Example 3, the embodiment of the present scheme introduces an appropriate amount of the compound of formula I and MMDS into the electrolyte to be used as additives, which can introduce functional groups such as amino groups and methylene groups in a directional manner into the CEI film formed at the positive electrode interface, thereby further improving the mechanical strength and thermal stability of the CEI film, improving the protective effect of the CEI film on the positive electrode, and further reducing the side reaction gas production between the positive electrode and the electrolyte at the same dosage.
[0094] From the test results of Examples 1, 6, 7, and 8, it can be seen that Compound I-1, Compound I-2, Compound I-3, and Compound I-4 have the same structure and functional groups as the compound of Formula I, so when used with MMDS as an additive, they can all achieve the effect of improving the high-temperature gas production of the battery. Therefore, the use of Formula I compounds with different types of R1, R2, R3, and R4 groups has little effect on the conductivity and high-temperature cycle performance of the battery.
[0095] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An electrolyte, characterized in that: including a lithium salt, a solvent, a first additive, and a second additive; The first additive comprises a compound represented by formula I: R1, R2, R3, and R4 in Formula I are each independently selected from a substituent having 1 to 6 carbon atoms, 0 to 4 unsaturations, and 0 to 3 heteroatoms, wherein the heteroatoms are selected from any one of nitrogen atoms, sulfur atoms, oxygen atoms, boron atoms, and phosphorus atoms; The second additive includes methylene methanedisulfonate.
2. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass content of the first additive is 0.05% to 3%, and the mass content of the second additive is 0.1% to 0.8%.
3. The electrolyte according to claim 2, characterized in that The mass content of the first additive in the electrolyte is 0.1% to 0.5%.
4. The electrolyte according to claim 1, characterized in that R1, R2, R3, and R4 in Formula I are each independently selected from an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group, or a heterocycle, and the heterocycle is selected from any one of pyridine, pyrrole, thiophene, thiazole, and furan.
5. The electrolyte according to claim 1 or 4, characterized in that The compound represented by formula I comprises at least one of the following compounds:
6. The electrolyte according to claim 1, characterized in that The electrolyte further includes a fourth additive, and the fourth additive is selected from at least one of fluoroethylene carbonate, propenyl-1,3-sultone, vinylene ester and tetravinylsilane.
7. The electrolyte according to claim 1, characterized in that The lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium acetate, lithium methanesulfonate and lithium trifluoromethylsulfonate; the mass content of the lithium salt in the electrolyte is 12% to 17%.
8. The electrolyte according to claim 1, characterized in that The solvent includes carbonate and carboxylate; the carbonate is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and fluoroethylene carbonate, and the carboxylate is selected from at least one of ethyl formate, ethyl acetate, propyl acetate and ethyl propionate; the mass content of the solvent in the electrolyte is 70% to 85%, and the mass content of the carboxylate in the electrolyte is above 30%.
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to any one of claims 1 to 8.
10. The secondary battery according to claim 9, characterized in that: The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes a lithium iron phosphate material; the solvent of the electrolyte includes a carboxylate, and the mass content of the carboxylate in the electrolyte is more than 30%.
Citation Information
Patent Citations
Methylene methanedisulfonate purification method
CN104926783A
Non-aqueous electrolyte and lithium-ion battery using same
CN105762410A
Electrolyte and battery
CN116706241A
Lithium ion battery electrolyte and lithium ion battery
CN117558987A
Device for producing nonaqueous electrolytic solution and method for producing nonaqueous electrolytic solution
JP2020068107A